2010
DOI: 10.1261/rna.2152710
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared (NIR) dye-labeled RNAs identify binding of ZBP1 to the noncoding Y3-RNA

Abstract: The analysis of protein-RNA association in vitro commonly involves radiolabeled in vitro transcribed RNAs. Nucleotides labeled with near-infrared (NIR) dyes provide promising alternatives for studying protein-RNA binding in vitro. However, it remained elusive whether random labeling of RNA probes by NIR dyes interferes with protein binding. Here, we demonstrate that infrared scanning allows the detection of randomly NIR-labeled RNA probes in the low femtomole range. The analyses of eight distinct protein-RNA c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 27 publications
(52 reference statements)
4
33
0
Order By: Relevance
“…Our finding that mY3 is required for complex formation, together with a recent report that hY1 and hY3 RNAs bind ZBP1 in vitro (Köhn et al 2010), suggests that since Ro interacts with the mY3 RNA terminal stem (Wolin and Steitz 1984;Pruijn et al 1991;Green et al 1998;Stein et al 2005), ZBP1 may bind sequences at the other end of FIGURE 6. mY3 RNA accumulates in nuclei when ZBP1 is depleted. (A,B) Wild-type fibroblasts were transfected with siRNAs against ZBP1 or control siRNAs as described for Figure 5.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Our finding that mY3 is required for complex formation, together with a recent report that hY1 and hY3 RNAs bind ZBP1 in vitro (Köhn et al 2010), suggests that since Ro interacts with the mY3 RNA terminal stem (Wolin and Steitz 1984;Pruijn et al 1991;Green et al 1998;Stein et al 2005), ZBP1 may bind sequences at the other end of FIGURE 6. mY3 RNA accumulates in nuclei when ZBP1 is depleted. (A,B) Wild-type fibroblasts were transfected with siRNAs against ZBP1 or control siRNAs as described for Figure 5.…”
Section: Discussionsupporting
confidence: 61%
“…One-way ANOVA test between the logarithms of the nuclear/cytoplasmic ratios of the mY3 FISH signals in siZBP1-treated vs. control cells (D,F) and between the mY1 and mY3 FISH signals in siZBP1-treated cells: P < 0.001. mY3, such as the large internal loop. Moreover, as the interaction of ZBP1 with hY3 RNA can be competed with a zipcode-containing RNA (Köhn et al 2010), the binding site on ZBP1 for Y3 RNA and the zipcode may overlap. Recent studies have shown that the third and fourth KH domains of ZBP1 form an antiparallel pseudodimer that interacts with a bipartite zipcode sequence from b-actin mRNA (Chao et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Western and Northern blotting were essentially performed as previously described (Kohn et al 2010. For antibodies and probes, see Supplemental Table S2.…”
Section: Western and Northern Blottingmentioning
confidence: 99%
“…There are, of course, other suitable labeling strategies, including body labeling by PCR or in vitro transcription with fluorescent nucleotide analogs (Besse et al 2009;Kohn et al 2010). Incorporation of amino, azido, or thiol groups during chemical synthesis of DNA or RNA oligonucleotides that can react with a wide variety of fluorescent dyes may also be used.…”
Section: -End Labeling Of Rnamentioning
confidence: 99%
“…Due to the challenges associated with using radioisotopes, fluorescent probes have become a favorable alternative in many biochemical assays (Royer and Scarlata 2008;LeTilly and Royer 1993;Aviv et al 2003;Ryder and Williamson 2004;Hardin and Batey 2006;Besse et al 2009;Kohn et al 2010). With modern instrumentation, the detection of fluorescent probes now rivals that of 32 P-labeled probes.…”
Section: Introductionmentioning
confidence: 99%